Bilateral Orocutaneous Fistula Secondary to Pericoronal Infection of Mandibular Third Molars: A Rare Case Report - Karina K. C.; Ankit Gupta Kalwar; Chandan Upadhyaha; Nitesh Chaurasia; Mamata Shakya (Clinical Case Reports)
ABSTRACT Odontogenic cutaneous fistulas are abnormal connections between the oral cavity and skin, often mistaken for skin infections. They typically result from dental infections but may also arise from salivary gland issues, tumors, or congenital anomalies. Accurate diagnosis is essential to prevent complications like infection, osteomyelitis, and discomfort. A 26‐year‐old woman presented with bilateral facial lesions and itching for the past year. Her symptoms began 5 years earlier with cheek pain and swelling, initially treated with antibiotics. Examination revealed pericoronitis of the mandibular third molars, leading to bilateral orocutaneous fistulas. Surgical removal of the affected teeth and fistulas was performed. Orocutaneous fistulas commonly result from long‐standing dental infections. Their location depends on the perforation site of the cortical plate. Early diagnosis through clinical examination and imaging is vital to prevent severe complications like osteomyelitis. Treatment involves addressing the underlying cause, typically through root canal therapy or tooth extraction. This case highlights the importance of early, interdisciplinary management of orocutaneous fistulas to prevent misdiagnosis, reduce discomfort, and avoid complications. Timely treatment ensures better outcomes and minimizes cosmetic concerns.